Evaluation of the dietitians adherence to nutrition support guidelines or protocols in Saudi hospitals and identifications of the barriers to compliance - Zaher, Sara; Alhussaini, Alhanouf Sameer; Abdulghani, Raneem Zuhair; Azzouni, Refal Eihab; Aalouh, Seba Khalid; Alharbi, Shahd Majed; Albukhari, Sondos (Frontiers in Nutrition, 2025)
BackgroundNutrition support (NS) is essential for patients who cannot meet their nutritional needs orally. To ensure the effective implementation of nutrition care, several NS guidelines have been established to standardise practices, enhance patient safety, and improve overall clinical outcomes. This study examined adherence to NS guidelines or protocols among dietitians in Saudi hospitals and identified key barriers to compliance.MethodologyAll dietitians working in hospitals across Saudi Arabia were eligible to participate in this cross-sectional study. Convenience sampling was used initially, followed by chain referral sampling, to achieve an adequate sample size. Data were collected via an online questionnaire between January and March 2025 and analysed using both univariate and multivariate analyses.ResultsA total of 133 participants were included in this study. The results showed that the American Society for Parenteral and Enteral Nutrition guidelines were the most commonly used, reported by 35.6% of respondents. Participants demonstrated equally strong adherence to protocols for both enteral nutrition and parenteral nutrition, with a median adherence score of 5.00. The most frequently reported challenges to adhering to NS protocols were resistance from healthcare practitioners (60.9%), limited resources (26.2%), and poor communication with the healthcare team (23.5%). Regression analysis revealed that both hospital size (β = 0.732, p = 0.001) and the dietitians’ years of experience (β = −0.344, p = 0.007) were significant predictors of adherence level.ConclusionThis study identified several barriers and challenges to adherence to NS guidelines or protocols. To improve NS practices, strategic investments in the improvement of hospital infrastructure, the development of structured interprofessional communication frameworks, and the implementation of ongoing training programs are needed. Addressing these key areas will be essential for standardising and optimising the delivery of nutrition care in hospitals across Saudi Arabia.